2015
DOI: 10.2319/031214-184.1
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of randomized controlled trials of interventions to improve adherence among orthodontic patients aged 12 to 18

Abstract: Objective: To investigate the effectiveness of interventions to enhance adherence among orthodontic patients aged 12 to 18 years. Specific adherence outcomes included were recall of information given by the orthodontic team, attendance at orthodontic appointments, self-reported oral hygiene behavior, and clinical indexes of oral hygiene. Materials and Methods: Electronic searches of Medline via OVID (January 1, 1966 through March 1, 2012), EMBASE, and the Cochrane central register of control trials from its in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…IM was proven to be a suitable method for developing health promotion programs for various health issues [64-66]. In the field of orthodontics, authors did not describe the process of program development explicitly in their publications [41,42,48-50,67-71]. This limited opportunities for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…IM was proven to be a suitable method for developing health promotion programs for various health issues [64-66]. In the field of orthodontics, authors did not describe the process of program development explicitly in their publications [41,42,48-50,67-71]. This limited opportunities for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic reviews and meta-analyses have found positive effects of interventions to reduce risk behavior among adolescents and young adults, including tobacco use [5-7], alcohol misuse [8-11], drug use [12,13], risky driving [8], and unsafe sex [14]; as well as interventions to promote health behaviors, such as use of contraception to prevent pregnancy [15-17], human papilloma virus (HPV) vaccination [18], oral health and hygiene [19,20], and nutrition and exercise promotion [21-23]. The widespread use of electronic communication technologies by young people, particularly the use of mobile phones and other mobile devices [24-26], presents new opportunities to intervene on risk and preventive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Few clinical evaluations of compliance exist in the literature. [24] The validity and reliability of Richter's clinical compliance evaluation form nor the modified form have been well established. A ceiling effect was observed with the MCCE and the patients in this study.…”
Section: Discussionmentioning
confidence: 99%